2015
DOI: 10.1297/cpe.24.175
|View full text |Cite
|
Sign up to set email alerts
|

Age at menarche and near final height after treatment with gonadotropin-releasing hormone agonist alone or combined with growth hormone in Korean girls with central precocious puberty

Abstract: Abstract.The use of a GnRH agonist (GnRHa) in central precocious puberty (CPP) is known to slow puberty progression, subsequently prevent early menarche, and attenuate the height loss caused by advanced skeletal maturation. But enhancing the final height has been so controversial that an additional approach has been used. We investigated the menarcheal age and near final height (NFH) in girls with CPP treated with GnRHa (N = 61) or GnRHa combined GH (N = 24). GnRHa was started at 8.1 ± 0.7 yr and administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
0
12
2
Order By: Relevance
“…However, this drug is expensive, and its cost is particularly high when combined with rhGH. In addition, improvements in final adult height (FAH) in CPP greatly varies [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this drug is expensive, and its cost is particularly high when combined with rhGH. In addition, improvements in final adult height (FAH) in CPP greatly varies [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…For girls with CPP who show a marked decrease in GV, evidence indicates that the addition of rhGH to GnRHa is significantly more effective in improving height, and PAH than GnRHa alone 12 . One very recent study published in 2015 reported the combined treatment group showed a greater height increment during treatment in Korean girls compared to the GnRHa alone group 46 . In 2003, Pucarelli and colleagues 47 found that the height gain in the combined treatment group was 6 cm higher than the GnRHa alone group.…”
Section: Discussionmentioning
confidence: 96%
“…In previous other studies, Partsch et al [ 22 ] reported that initial BA advancement and treatment duration were factors that explained 68% of height gain. Other studies found that MPH, CA, pretreatment height, height at the end of treatment, and growth rate during treatment were factors influencing near final height [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%